Preparing muslims with diabetes mellitus for Ramadan fasting in Singapore: a clinical approach and review of current practice - Sueziani Binte Zainudin; Ester Yeoh (Singapore Medical Journal)
Ramadan fasting, a month-long annual practice for Muslims, can be challenging for those who have diabetes mellitus with or without associated complications or pre-existing comorbidities, as well as healthcare providers involved in their care. Inadequate preparation for this fasting period can result in increased complications. We reviewed the current practice of Muslims with diabetes mellitus in Singapore who intend to fast during Ramadan, with particular attention on locally available evidence. Adequate preparation for Ramadan fasting, including pre-Ramadan assessment, optimisation of glycaemic control, structured Ramadan-focused diabetes education, medication adjustment, glucose monitoring and test fasting, can lead to benefits in terms of improvements in metabolic control and reduced risk of fasting-related complications in people with diabetes mellitus. While there are ongoing efforts to reduce risk during this period, larger-scale national programmes are needed to avert complications and assess the long-term effects of Ramadan fasting in the local population.